A novel approach for preload measurement and analysis of fixed position preload spindle. (May 2019) - Li, Jiandong; Zhu, Yongsheng; Yan, Ke; Yan, Xiaoyun; Hong, Jun
Spindle preload has a decisive influence on the performance of precision machine tool spindle and is usually defined as a constant parameter in most theoretical studies. In fact, the spindle preload changes with the operating conditions, such as temperature and speed of spindle. An in-depth understanding of preload variation mechanism becomes important for preload optimization and adjustment. Although some scholars have theoretically studied the relationship between operating conditions and preload, the results lack experimental verification since there is no effective way to measure the preload on-line. In this paper, a special pressure transducer for the preload continuous measurement of fixed position preload spindle was proposed, and the coupling effect of temperature and speed on the preload was experimentally tested and theoretically simulated based on the finite-element-method-based thermo-mechanical model considering the nonlinearity of bearing stiffness. The results show that the spindle speed contributes to the increase of the spindle preload, while the temperature causes a decrease of the preload. The preload variation is the trade-off effect of temperature and speed on it. The deformation of the spacer caused by temperature and speed is the most important factor leading to the change of the spindle preload.